Interpretation and gap filling in iInternational commercial contracts / Ayse Nihan Karadayi Yalim. - Yalim, Ayse Nihan Karadayi (Intersentia, 2019)
With the growth of cross-border business, the rather important but complex and controversial topic of interpretation and gap filling in international commercial contracts receives more and more attention. International legal instruments such as CISG, UNIDROIT Principles, PECL and DCFR provide rules in order to interpret international commercial contracts in a uniform way. However, while these instruments may bring together already existing national concepts, they must of course be understood beyond the domestic concepts and approaches as such. This book is an autonomous comparison across the above-mentioned international legal instruments, with a focus on the rules on interpretation and gap filling that provides the necessary theoretical background and case law to understand the rules in practice. Interpretation and Gap Filling in International Commercial Contracts examines the uniform and harmonised set of rules in their own right; without comparison to national laws, but in their own unique setting of international commercial contracts. It is a practical user guide for both scholars and practitioners. Dr Ayse Nihan Karadayi is a postdoctoral researcher on international contract law at the University of Antwerp, Belgium.